Evolutionary ontology : reclaiming the value of nature by transforming culture - Šmajs, Josef (Value inquiry book series, 2008)
This book examines new concept of evolutionary ontology based on the idea of radically different ¿ontic orders¿ ¿ natural and cultural being. It explains how culture evolved out of nature and how it became ¿anti-natural¿. The remedy is seen in the global biophilous reconstruction of culture. The value of the ¿live planet¿ Earth and the ¿subject¿ capable of creative activity and evolution are given fundamental philosophical interpretation.